KEY INFORMATION AND COMMUNICATION TECHNOLOGIES AS AN IMPORTANT FACTOR IN IMPROVING THE EFFICIENCY OF SUPPLY CHAINS IN THE FASHION INDUSTRY - N. Yu. Barkova (Вестник университета)
The article considers key information and communication technologies used in the supply chains of the fashion industry. The author segmented these technologies into several groups, including selected programs that ensure effective communication between the company’s functional departments and supply chain links; software resources aimed at maintaining logistics operations, such as production, warehousing, cargo transportation; operational and strategic planning systems. The main purpose of the considered information technologies is to take into account the specific characteristics of the “fashion” business, such as a high range and a short product life cycle, the need to take into account the rapidly changing requirements of buyers of goods in the fashion industry, the geographical distribution of supply chain participants. The author performs a review of key software products and technologies that improve the efficiency of business process management in the supply chains of the fashion industry, including CAD and CAM systems, ERP systems on the example of SAP AFS, SAP Fashion Management and some other software resources and technologies.